Scientific and methodological racommendations by the body of management of the border guard unit regarding the constraction of the subsystem of technical monitoring of the surface situation on the seafront is responsibility - Mazur, V. Yu.; Kupriyenko D. А.; Borovyk О. V. (Honor and Law, 2019)
The scientific and methodical recommendations for border control unit management bodies on the construction of a subsystem of technical monitoring of the surface conditions at the maritime liability area, which are proposed to be used during preparation for operational and service activities, have been developed. At the same time, as a criterion for the optimal construction of a technical monitoring subsystem, a criterion for minimizing the time-consuming costs to cover a specific liability area is selected, while ensuring the requirements for the functional adequacy, stability and suitability of the components of this subsystem.